Samoa : Technical Assistance Report-Report on the External Sector Statistics Assistance Mission. (IMF Staff Country Reports; Country Report, 2019)
This report discusses the report of technical assistance mission to support the Central Bank of Samoa (CBS) in further strengthening external sector statistics compilation and dissemination. The mission recommended that ESS compilers convert to using the International Merchandise Trade Statistics (IMTS) data as the source of exports data starting 2019; and adjust historical data at least as far back as 2014. Also, it would be beneficial to switch the source of trade in goods exports from exchange control records to Customs data to ensure better coverage and improve consistency with the IMTS published by the Samoa Bureau of Statistics. The CBS should adopt a step-by-step approach for the collection of offshore units' data, initially focusing on offshore banks. As international requirements for the reporting of offshore units evolves, it is likely that the Samoa International Finance Authority (SIFA) and the offshore company trustees will need to expand data collection from the offshore units under their jurisdiction. The CBS should, therefore, keep abreast of developments with respect to offshore reporting and continue to liaise with the SIFA.